Hukum Pernikahan dalam Islam: Analisis Perbandingan Konteks Menurut 4 Mazhab - Nurhasnah, Nurhasnah (Indonesian Journal Publisher, 2024)
Lately, there have been numerous marriage cases in Indonesia, including underage marriages, domestic violence, partner selection without proper knowledge of marriage. Therefore, it is important for all segments of society to be aware of the legal aspects of marriage for an individual. Hence, a study has been conducted with the theme